Antibacterial and biofilm disruptive nonribosomal lipopeptides from Streptomyces parvulus against multidrug-resistant bacterial infections - Shine Kadaikunnan; P. Vijayaragavan; M.A. Rathi; Balasubramanian Balamuralikrishnan; Naiyf S. Alharbi; V.K. Gopalakrishnan; Sumitha Purushothaman; Ravikumar Sivanesan (Elsevier, 2024)
Background: In recent years, new drugs for the treatment of various diseases, thereby the emergence of antimicrobial resistance tremendously increased because of the increased consumption rate of various drugs. However, the irrational use of antibiotics increases the microbial resistance along with that the frequency of mortality associated with infections is higher. Broad-spectrum antibiotics were effectively against various bacteria and the unrestricted application of antibiotics lead to the emergence of drug resistance. The present study was aimed to detect the antibacterial properties of lipopeptide novel drug producing Streptomyces parvulus. Methods: A lipopeptide-producing S. parvulus was isolated from the soil sample. The inhibitory effect of lipopeptide was detected against Gram-positive and Gram-negative bacteria. Bactericidal activity and minimum inhibitory concentration (MIC) were assayed. The IC50 value was analysed against ovarian and human melanoma cell lines. The experimental mouse model was infected withKlebsiella pneumoniae and treated with lipopeptide and bactericidal activity was determined. Results: The results indicated that the antibacterial activity of lipopeptide ranges from 13 ± 1 mm to 32 ± 2 mm against Gram-positive and Gram-negative strains. The lowest MIC value was noted as 1.5 ± 0.1 µg/mL against K. pneumoniae and the highest against E. aerogenes (7.5 ± 0.2 µg/mL). The IC50 value was considerably high for the ovarian cell lines and human melanoma cell lines (426 µg/mL and 503 µg/mL). At 25 µg/mL concentration of lipopeptide, only 16.4% inhibition was observed in the ovarian cell line whereas 20.2% inhibition was achieved at this concentration in the human melanoma cell line. Lipopeptide inhibited bacterial growth and was completely inhibited at a concentration of 20 µg/mL. Lipopeptide reduced bacterial load in experimental mice compared to control (p < 0.05). Conclusion: Lipopeptide activity and its non-toxic nature reveal that it may serve as a lead molecule in the development of a novel drug.